ACTION DIALOGUE IN CTRS ECO BHINNEKA MUHAMMADIYAH IN MAINTAINING HARMONY THROUGH ENVIRONMENTAL PRESERVATION IN THE CITY OF PONTIANAK - Bustomi, Yazid Imam; Wahyudhi, Syukron; Hj Osmara, Nurninashahawana (Jurnal Studi Agama dan Masyarakat, 2023)
The purpose of this study is to determine the form, foundation, and implications of the action dialogue on Cycling to Religious Sites carried out by Eco Bhinneka Muhammadiyah in maintaining harmony through environmental preservation in Pontianak City. The research method used is a qualitative approach with a descriptive-analysis type. The source of data used in this study was found by being a participant observer and interviews with regional managers, field staff, and Eco Bhinneka managers representing their respective religions. Then some terms of reference documents, proposals, documentation on social media, and activity documentation. Based on the results of data analysis, it was found that religion has an important role as a unifier in religious communities in Pontianak. The holding of an action dialogue at Cycling to Religious Sites (CTRS) can be declared capable of realizing harmony through environmental conservation in Pontianak City. The implementation of these actions is in the form of visits to houses of worship, giving plant seeds, providing sorting bins, and free health checks. Then considering that Eco Bhinneka courtiers come from interfaith youths, they have a theological foundation, and also a social basis looking at the current condition of society. Furthermore, these activities have implications for harmony and environmental preservation by increasing the intensity of interaction by visiting houses of worship and the interaction is more ecological as evidenced by Greening in the environment of houses of worship by being given dozens of plant seeds.